Process for preparing hydrotreating catalyst
By grinding and recombining the catalyst fine powder, and conducting heat treatment and recovery agent contact, the problems of high energy consumption and low resource utilization efficiency in the preparation process of the existing hydrotreatment catalyst are solved, and catalyst activity recovery and resource utilization efficiency are improved.
Patent Information
- Application Number
- CN202380064156.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-09
- Filing Date
- 2023-09-07
- Publication Date
- 2025-04-15
AI Technical Summary
The preparation process of existing hydrotreatment catalysts consumes high energy, low resource utilization efficiency, and limited regeneration and recovery technologies, resulting in reduced catalyst activity and increased waste.
The catalyst activity is restored by grinding the fine powder for hydrotreatment and mixing it with the binder, heat treatment and contacting the recovery agent.
This method can effectively restore the activity of the catalyst, improve resource utilization, and reduce waste generation, and the HDS and HDN activities of the catalyst can reach 60-90% of the commercial catalyst.
Smart Images

Figure CN119836324A_ABST
Abstract
Description
Background Art Technical Field
[0001] The present invention relates to a method for preparing a hydroprocessing catalyst, a hydroprocessing catalyst obtainable by said method and a method for hydroprocessing a hydrocarbon feedstock using said hydroprocessing catalyst.
[0002] Description of Background Art
[0003] In general, the purpose of catalytic hydroprocessing of hydrocarbonaceous raw materials is to remove impurities. Common impurities include sulfur compounds and nitrogen compounds. At least partially removing such impurities from the raw materials will ensure that less sulfur oxides and / or nitrogen oxides harmful to the environment will be released when the final product burns. In addition, sulfur compounds and nitrogen compounds are poisonous to many catalysts used to convert raw materials into ready-to-use products in the oil industry. Examples of such catalysts include cracking catalysts, hydrocracking catalysts and reforming catalysts. Therefore, raw materials are usually subjected to catalytic hydroprocessing before processing in, for example, a cracking unit.
[0004] Catalytic hydrotreating means contacting the feedstock with hydrogen at elevated temperature and pressure in the presence of a hydrotreating catalyst. In this process, sulfur compounds and nitrogen compounds present in the feedstock are converted into easily removable hydrogen sulfide and ammonia, respectively, in processes known as hydrodesulfurization and hydrodenitrogenation.
[0005] In general, hydroprocessing catalysts consist of a support on which a Group VI metal component and a Group VIII metal component are deposited. The most commonly used Group VI metals are molybdenum and tungsten, while cobalt and nickel are conventional Group VIII metals. Phosphorus may also be present in the catalyst. Hydroprocessing catalysts are typically shaped, for example in the form of extrudates.
[0006] Prior art methods for preparing these catalysts are characterized by compounding the support material with the hydrogenation metal components, for example by impregnation, followed by calcination of the composite to convert the metal components into their oxides. Prior to use in hydroprocessing, the catalysts are usually presulfided to convert the hydrogenation metals into their sulfides.
[0007] The preparation of hydroprocessing catalysts is an energy-intensive process that requires the extensive use of expensive natural resources such as molybdenum, cobalt, nickel and aluminum.
[0008] A problem that may arise during catalyst shaping during catalyst preparation is the formation of by-products of unusable catalyst materials. These unusable materials include, for example, catalyst fines from, for example, support production, fresh catalyst production, catalyst regeneration or (damaged) extrudates, which do not meet the length specifications required by the refiner to prevent excessive pressure drops in its equipment. The formation of such unusable catalytic materials results in an inefficient use of raw materials. There is still a need to improve the utilization of resources and reduce the amount of waste.
[0009] Spent catalysts are used catalysts that have reacted during the hydroprocessing process and are no longer available for catalysis, and they are usually sent to landfills for disposal. The regeneration of used catalysts involves thermal treatment to burn off coke and / or sulfur deposits, which can only restore the activity of the used catalyst to a certain extent. In addition, mechanical wear of the catalyst, mechanical damage during material processing and / or internal transportation of the equipment, and repeated harsh reaction conditions during hydroprocessing and / or regeneration may damage the required extrudate length. The reduction of extrudate length with continuous hydroprocessing / regeneration procedures inevitably leads to an increase in pressure drop in the reactor. This is unacceptable for refiners constrained by hydraulic pressure and acceptable pressure distribution. Therefore, the reactivation of used catalysts is limited, and refiners still rely heavily on the continuous supply of freshly prepared hydroprocessing catalysts.
[0010] In addition to regeneration, the spent catalyst may also undergo a recovery process, which involves contacting the regenerated spent catalyst with an organic additive and / or an acid. These recovery processes may further restore the activity of the spent catalyst. However, the recovery process cannot be used endlessly to restore the regenerated catalyst. After a certain number of recovery, the catalyst can no longer be used in the hydroprocessing process and faces recycling to recover the metals.
[0011] US4107087 describes a method for preparing a hydroprocessing catalyst from silica / alumina catalyst fines, comprising: A. adding 1.0 to 15.0% by weight of citric acid to an aqueous slurry of the silica / alumina catalyst fines, the fines being silica / alumina hydroprocessing catalyst fines impregnated with: (1) a metal selected from the group consisting of iron, cobalt, nickel, palladium and platinum; and (2) a metal selected from the group consisting of chromium, molybdenum, tungsten, selenium and tellurium; B. mixing, filtering, drying, extruding and calcining to form a hydroprocessing catalyst. These fines are produced by attrition and fracturing during the preparation of fresh catalysts, or are recovered from regenerated or spent catalysts. It is reported that the addition of citric acid to large quantities of catalyst fines allows them to be incorporated into catalyst formulations without loss of important physical properties.
[0012] M. Marafi et al., Catalysis Today 130 (2008) 421-428, "Preparation of heavy oil hydrotreating catalyst from spent residue hydroprocessing catalysts", describe a method for recycling spent hydroprocessing catalysts containing high levels of vanadium. Spent catalyst extrudates containing different levels of V, Mo and Ni on Al2O3 were subjected to different treatments, such as washing, decoking, acid leaching and hydrothermal treatment. The treated spent catalyst was crushed and ground into a fine powder, and new hydroprocessing catalysts were prepared by mixing the spent catalyst powder with boehmite in different proportions, followed by peptization, kneading and extrusion, drying and calcination. Acid leaching and hydrothermal leaching significantly reduced the metal content, but favored the removal of V from the pore openings to clear the pores. It was found that in the case where the spent catalyst treated in this way is used to prepare a new catalyst having large pores, a relatively high surface area and pore volume, and high activity in promoting HDM and HDS reactions, 40-60% by weight of the spent catalyst can be added to the boehmite. The disadvantage of this method is that it is optimized to reduce the adverse effects of vanadium and although it provides some recovery of activity, it results in high losses of active metals and recovery of activity is lower than desired. Also, many more processing steps are required to leach and recover the leached metals.
[0013] WO2012021386 describes a method for preparing a hydroprocessing catalyst from spent catalyst fines. The catalyst fines used in the present invention are prepared from spent hydroprocessing catalyst or regenerated hydroprocessing catalyst or recycled but unused hydroprocessing catalyst. The method comprises forming a shaped support from an inorganic oxide powder and catalyst fines, wherein the catalyst fines are present in the shaped support in an amount ranging from up to about 50% by weight of the shaped support, and wherein the shaped support is dried and calcined; a metal-containing solution is incorporated into the shaped support to provide a metal-incorporated support; the metal-incorporated support is dried so as to provide a dried metal-incorporated support having a volatile content in the range of 1 to 20% by weight LOI; a polar additive is incorporated into the dried metal-incorporated support to provide an additive-impregnated composition; and a chelating agent is incorporated into the shaped support or into the dried metal-incorporated support. It is described that a problem with using ground catalyst fines in the preparation of new catalysts is that they may contribute to catalysts having macropores (diameters greater than 100 μm) contained in the catalyst that are much larger than would be the case if ground catalyst fines were not used (i.e., when the new catalyst was prepared from virgin material). ) in the pore volume percentage. Such a higher macropore volume percentage may contribute to reduced catalyst activity. Therefore, the amount of fine powder used in the catalyst is less than 50% by weight, and most preferably 15% to 35% by weight.
[0014] With increasing regulations and societal expectations for industry to be more sustainable, there is a need for improved reactivation methods that allow catalysts to function catalytically longer. There is also a need for methods that allow for more efficient recycling of metals to reduce the use of dwindling natural resources and reduce waste that ends up in landfills. There is also a need to reduce carbon emissions in the petroleum industry.
[0015] It is an object of the present invention to solve at least one of the above problems.
[0016] It is also an object of the present invention to provide an improved process for reactivating spent hydroprocessing catalysts or spent fresh catalytic material and to provide a process for preparing hydroprocessing catalysts from such spent hydroprocessing catalysts or spent fresh catalytic material.
[0017] In a further aspect, the present invention relates to a hydroprocessing catalyst obtainable by the improved process and its use in a hydroprocessing process. Summary of the invention
[0018] While the invention is defined in the independent claim, further aspects of the invention are set out in the dependent claims and the following description.
[0019] According to the present invention, there is provided a method for preparing a hydroprocessing catalyst, the method comprising
[0020] a) providing a first hydroprocessing catalyst comprising a Group VI metal and a Group VIII metal selected from the group consisting of fresh catalyst, regenerated catalyst, restored catalyst, fresh, regenerated or restored catalyst fines, or mixtures thereof;
[0021] b) grinding the hydroprocessing catalyst to form catalyst fines, unless the first hydroprocessing catalyst already consists of fresh, regenerated or rejuvenated catalyst fines or mixtures thereof;
[0022] c) mixing the catalyst fines with at least a binder to form a mixture, wherein optionally the mixing and grinding are at least partially combined, and wherein optionally during the mixing a first hydroprocessing catalyst consisting of fresh, regenerated or rejuvenated catalyst fines is added after grinding; wherein the mixture comprises at least 60 wt% catalyst fines based on the dry weight of the mixture;
[0023] d) shaping the mixture;
[0024] e) heat treating the shaped mixture;
[0025] f) contacting the heat treated molding mixture with a restoring agent.
[0026] In a preferred embodiment, the method further comprises a step g) of contacting the heat treated shaped mixture with a solution comprising a Group VI and / or Group VIII metal and optionally a phosphor compound, wherein step g) can be performed before, during or after step f), or wherein the Group VI and / or Group VIII metal is added to the mixture before shaping the mixture.
[0027] In a preferred embodiment, the solution comprises a Group VI and / or Group VIII metal in such an amount that after contacting, the heat treated shaped mixture comprises a metal concentration of at least 90 wt %, preferably at least 95 wt %, more preferably at least 98 wt % of the metal concentration in the first hydroprocessing catalyst (in wt % of metal oxide), so that the activity of the original fresh first hydroprocessing catalyst as the source of the catalyst fines is restored as much as possible. In step g), the metal is preferably added so that the catalyst comprises 5-40 wt %, preferably 10-38 wt %, more preferably 15-35 wt % of the Group VI metal calculated as trioxide and 1-10 wt %, preferably 2-8 wt % of the Group VIII metal calculated as oxide, and preferably also comprises 1-10 wt % of phosphorus calculated as P2O5. An advantage of the present invention is that only relatively small amounts of metal or phosphorus need to be added, so it is also easier to add the metal and the restoring agent in one step rather than two or more consecutive impregnation steps.
[0028] In a preferred embodiment, step g) of contacting the heat treated shaped mixture with a solution comprising a Group VI and / or Group VIII metal is performed during step f), and preferably the solution comprising a Group VI and / or Group VIII metal also comprises a restoring agent.
[0029] In a preferred embodiment, the first hydroprocessing catalyst comprises a regenerated catalyst obtained by regenerating a spent catalyst.Preferably, the first hydroprocessing catalyst comprises low levels of metal contaminants, particularly preferably the amount of vanadium on the catalyst is less than 2 wt%, preferably less than 1 wt%.
[0030] According to another preferred embodiment, the mixture comprises at least 70 wt.-%, preferably at least 80 wt.-%, more preferably at least 85 wt.-%, even more preferably at least 90 wt.-%, most preferably at least 95 wt.-% catalyst fines based on the dry weight of the mixture.
[0031] In another preferred embodiment, the binder comprises an inorganic oxide, preferably one or more selected from the group consisting of alumina, silica, silica-alumina, magnesia, combinations thereof, salts thereof and clay, preferably alumina or alumina-silica, most preferably gamma-alumina. Its salts may have inorganic anions or organic anions.
[0032] In a preferred embodiment, the binder comprises a material similar to the binder material in the first hydroprocessing catalyst, and thus the binder in the mixture is the same as the support material or binder material of the first hydroprocessing catalyst.
[0033] In another preferred embodiment, the D50 particle size of the catalyst fines is less than 200 μm, preferably less than 100 μm, more preferably less than 50 μm, even more preferably less than 30 μm, and preferably greater than 1 μm, more preferably greater than 2 μm, and even more preferably greater than 4 μm. If the first hydroprocessing catalyst does not have this preferred D50 particle size, it is ground to form catalyst fines having a D50 particle size within the stated range.
[0034] In a preferred embodiment, the catalyst fines in the mixture have a D90 particle size of less than 500 μm, preferably less than 200 μm, more preferably less than 100 μm, and even more preferably less than 80 μm. D90 is preferably greater than 1 μm, more preferably greater than 2 μm, and even more preferably greater than 4 μm.
[0035] In a preferred embodiment, the method according to the invention further comprises an aging step h) after the recovery step f), wherein the aging is preferably carried out at a temperature between 20° C. and 100° C., preferably between 30° C. and 80° C., and preferably for a time of less than 18 hours, preferably less than 15, 10, 7, 4 hours or even less than 2 hours. In a preferred embodiment, the aging is carried out for a time of between 0.5 and 2 hours, preferably between 0.5 and 1 hour.
[0036] In yet another preferred embodiment, the restoring agent reduces the crystalline fraction of the metal oxide in the heat-treated shaped mixture, preferably by at least 20%, preferably by at least 30%, or more preferably by at least 40%.
[0037] In a preferred embodiment, the restoring agent comprises a complexing agent, preferably a carboxylic acid comprising at least one carboxyl group and 1 to 20 carbon atoms.
[0038] In the most preferred embodiment, the complexing agent is citric acid or lactic acid.
[0039] In another preferred embodiment, the restoring agent further comprises an organic additive, wherein the organic additive is preferably selected from compounds containing at least two hydroxyl groups and 2 to 10 carbon atoms per molecule and ethers or polyethers of these compounds. In this case, the OH groups in the carboxylic acid are not considered to be hydroxyl groups. Preferably, the restoring agent is a combination of lactic acid or citric acid and an organic additive.
[0040] The invention furthermore relates to a hydroprocessing catalyst obtainable by the process according to the invention.
[0041] In a preferred embodiment, the hydrotreating catalyst obtainable by the process according to the present invention comprises a total pore volume of 0.2 to 1.0 mL / g, preferably 0.3-0.7 mL / g, more preferably 0.3-0.6 mL / g.
[0042] The hydrotreating catalyst obtainable by the process according to the invention preferably has a typical macropore volume of 0.005-0.3 mL / g, preferably a macropore volume of less than 0.1 mL / g, preferably less than 0.06 mL / g. In this context, pores with a diameter greater than 100 nm are considered macropores.
[0043] The hydroprocessing catalyst obtainable by the process according to the invention preferably has a 2 The hydroprocessing catalyst preferably has a side crush strength (SCS) of at least 2 lbs / mm, more preferably at least 3 lbs / mm, and even more preferably at least 4 lbs / mm.
[0044] When additional metals are added to the catalyst as described above, the total pore volume and macropore volume of the heat-treated shaped mixture to be used as a support for the catalyst may be higher than the total pore volume and macropore volume of the catalyst, but are generally still within the above ranges. The present invention also relates to a heat-treated shaped mixture for use as a support in the preparation of a catalyst, comprising: at least 80%, preferably at least 85% by weight of catalyst fines; a total pore volume (TPV) of 0.3-0.7 mL / g, more preferably 0.3-0.6 mL / g; 0.005-0.15, preferably 0.005-0.1 mL / g, more preferably 0.005-0.06 mL / g; Macropore volume above 120 and 300m 2 / g, preferably between 145 and 280m 2 / g, and preferably at least 2 lbs / mm, more preferably at least 3 and even more preferably at least 4 lbs / mm of side crush strength (SCS). In this article, > The macropore volume is the diameter greater than The volume in the hole. Figure 1The prior art carrier showed that it had a mass of about 0.18 mL / g. Macropore volume. The prior art >100 nm macropores are about 0.14 ml / g, while the >100 nm macropores of support C2 are about 0.09 ml / g, and the >100 nm macropores of support C7 are about 0.05 ml / g.
[0045] The present invention also relates to a process for hydrotreating a hydrocarbon feedstock, wherein the hydrocarbon feedstock is contacted under hydrotreating conditions with a catalyst according to the present invention, said catalyst being obtainable by the process according to the present invention, which has optionally been dried before contacting with the hydrocarbon feedstock, and which has optionally been (pre)sulfurized. Preferably, the above catalyst is used for the hydrotreating of diesel, naphtha or VGO feedstocks. DETAILED DESCRIPTION
[0046] The above object is achieved by providing a method for preparing a hydroprocessing catalyst, the method comprising:
[0047] a) providing a first hydroprocessing catalyst comprising a Group VI metal and a Group VIII metal selected from the group consisting of fresh catalyst, regenerated catalyst, restored catalyst, fresh, regenerated or restored catalyst fines, or mixtures thereof;
[0048] b) grinding the hydroprocessing catalyst to form catalyst fines, unless the first hydroprocessing catalyst already consists of fresh, regenerated or rejuvenated catalyst fines or mixtures thereof;
[0049] c) mixing the catalyst fines with at least a binder to form a mixture; wherein optionally the mixing and grinding are at least partially combined, and wherein optionally during the mixing a first hydroprocessing catalyst consisting of fresh, regenerated or rejuvenated catalyst fines is added after grinding, wherein the mixture comprises at least 60 wt% catalyst fines based on the dry weight of the mixture;
[0050] d) shaping the mixture to form a shaped mixture;
[0051] e) heat treating the shaped mixture;
[0052] f) contacting the heat treated molding mixture with a restoring agent.
[0053] The starting material for the process according to the invention is a first hydroprocessing catalyst. The first hydroprocessing catalyst comprises a Group VI metal and a Group VIII metal. As Group VI metals, molybdenum, tungsten and chromium may be mentioned, with molybdenum or tungsten being preferred. Molybdenum is particularly preferred. Group VIII metals include nickel, cobalt and iron. Nickel, cobalt or a combination thereof is preferred.
[0054] In hydroprocessing catalysts, the Group VI metal and Group VIII metal content is usually calculated as their metal oxides. The metal content in the catalyst can be determined by X-ray fluorescence spectroscopy (XRF) or inductively coupled plasma spectroscopy (ICP). The content is calculated as metal oxide, expressed as a weight percentage relative to the total dry weight of the catalyst.
[0055] The metal content of the hydroprocessing catalyst is usually in the range of 0.1 to 50 wt % based on the total weight of the catalyst, calculated as oxide. Calculated as trioxide, the metal component of Group VI is usually present in an amount of 5-40 wt %, preferably 10-38 wt %, more preferably 15-35 wt %. Calculated as oxide, the metal component of Group VIII is usually present in an amount of 1-10 wt %, preferably 2-8 wt %. If it is really necessary, the catalyst can also contain other components, such as phosphorus, halogen (e.g., fluorine) and boron. In particular, it is preferred that phosphorus calculated as 1-10 wt % by P2O5 be present to improve the hydrodenitrogenation activity of the catalyst.
[0056] In the hydroprocessing catalyst, the metal is composited with a carrier. The catalyst carrier may comprise conventional inorganic oxides, such as alumina, silica, silica-alumina, alumina in which silica-alumina is dispersed, alumina coated with silica, magnesia, zirconium oxide, boron oxide and titanium dioxide, and mixtures of these oxides. Generally speaking, preference is given to carriers that are alumina, silica-alumina, alumina in which silica-alumina is dispersed, or alumina coated with silica. Alumina and alumina containing up to 10% by weight of silica are particularly preferred. Preferred within this group are carriers containing transition alumina (e.g., η, θ or γ alumina), with γ-alumina carriers being the most particularly preferred. In the method of the present invention, the above-mentioned carrier material may be used as a binder and mixed with a hydroprocessing catalyst fine powder to prepare the catalyst of the present invention.
[0057] The hydroprocessing catalysts are conventionally used in the hydroprocessing process in the form of spheres, pellets or extrudates. Examples of suitable types of extrudates are disclosed in the literature (see in particular US Pat. No. 4,028,227).
[0058] The starting material may be a fresh hydroprocessing catalyst. The term fresh refers to a catalyst that has not yet been used in a hydroprocessing process. Fresh hydroprocessing catalysts may be prepared according to conventional catalyst preparation methods known to the skilled person. Prior to use in hydroprocessing, the catalyst is typically presulfided to convert the metals into their sulfide forms.
[0059] Fresh hydroprocessing catalysts may also be prepared according to a process comprising a further activation step, for example comprising a step in which the catalyst is contacted with an organic additive and / or an acid.
[0060] Catalyst fines of the fresh first hydroprocessing catalyst may be generated during production, handling, storage, or transportation of the fresh first hydroprocessing catalyst prior to use in a hydroprocessing process.
[0061] However, the starting material for the process of the invention may also advantageously be a used hydroprocessing catalyst (also referred to as spent hydroprocessing catalyst) which has been regenerated by removing coke therefrom. In this case, the catalyst may or may not have contained additives before its first use. The used hydroprocessing catalyst may also be subjected to a further recovery or activation step which involves contacting the regenerated used catalyst with an organic additive and / or an acid.
[0062] Regeneration is carried out by contacting the used hydroprocessing catalyst with an oxygen-containing gas under such conditions that the carbon content of the regenerated catalyst is generally less than 3% by weight, preferably less than 2% by weight, and more preferably less than 1% by weight. After regeneration, the sulfur content of the catalyst is generally less than 2% by weight, preferably less than 1% by weight. Before the regeneration step, the carbon content of the catalyst is generally greater than 5% by weight, typically between 5 and 25% by weight. The sulfur content of the catalyst before the regeneration step is generally greater than 5% by weight, typically between 5 and 20% by weight.
[0063] The maximum catalyst temperature during the regeneration step will be determined by the properties of the catalyst to be regenerated and the limitations of the method, and in principle a higher maximum temperature is preferred because it allows the regeneration time to be shortened. A long regeneration time means a long residence time of the catalyst material in the regeneration reactor, which leads to the breakage of the catalyst material. However, high regeneration temperatures risk the formation of large grains and metal sintering that results in a loss of metal surface area. Catalysts with higher metal contents generally require lower maximum catalyst temperatures than catalysts with lower metal contents. Typically, the maximum catalyst temperature during the regeneration process is at most 650°C, preferably at most 575°C, more preferably at most 550°C, and even more preferably at most 525°C.
[0064] The maximum catalyst temperature during the regeneration process is generally at least 300°C, preferably at least 350°C, more preferably at least 400°C, still more preferably at least 450°C.
[0065] It is noted that in this specification, except when explicitly stated otherwise, any temperature given relates to the temperature of the catalyst. The catalyst temperature can be determined in any manner known to the skilled person, for example by means of appropriately placed thermocouples.
[0066] Preferably, the regeneration step in the presence of oxygen is carried out in two steps, i.e. a first lower temperature step and a second higher temperature step. In the first lower temperature step, the catalyst is contacted with the oxygen-containing gas at a temperature of 100 to 370° C., preferably 175 to 370° C. In the second higher temperature regeneration step, the catalyst is contacted with the oxygen-containing gas at a temperature of 300 to 650° C., preferably 320 to 550° C., still more preferably 350-525° C. The temperature during the second step is preferably at least 10° C., more preferably at least 20° C. higher than the temperature of the first step discussed above. The temperature range refers to the set temperature of the oxygen-containing gas. Taking into account the above indications, it is well within the capabilities of the skilled person to determine the appropriate temperature range.
[0067] The catalyst is preferably regenerated using a moving bed process, preferably (if applicable) with a bed thickness of 1 to 15 cm. In the context of this specification, the term "moving bed" means all processes in which the catalyst is in motion compared to the apparatus, including ebullating bed processes, fluidized processes, processes in which the catalyst rotates through the apparatus (e.g. rotating shutters) and all other processes in which the catalyst is in motion.
[0068] The duration of the regeneration process including stripping will depend on the nature of the catalyst and the exact way in which the process is carried out, but is generally between 0.25 and 24 hours, preferably between 0.5 and 16 hours.
[0069] EP1680486 describes a method of activating a hydroprocessing catalyst, the method comprising contacting a hydroprocessing catalyst comprising a Group VI metal oxide and a Group VIII metal oxide with an acid and an organic additive, wherein the hydroprocessing catalyst may be a used hydroprocessing catalyst that has been regenerated, or wherein the hydroprocessing catalyst is a fresh hydroprocessing catalyst.
[0070] The spent hydroprocessing catalyst may have been used once in the hydroprocessing process, but may have undergone several cycles of hydroprocessing followed by regeneration and / or recovery steps. The regeneration process is usually repeated as frequently as possible to avoid having to recycle the catalyst to recover the metal. However, during this regeneration process, the catalyst particles are destroyed and catalyst fines and broken catalyst particles (extrudates) are produced, which can be screened out for use in the method of the present invention. At a certain point in time after several regeneration steps, the properties of the regenerated spent catalyst may have deteriorated to such an extent that it is beneficial to grind them into catalyst fines for the method of the present invention. The advantage of the present invention is that very high weight % catalyst fines can be used and a very high percentage of the original activity can be recovered, so that the above-mentioned problems associated with repeated regeneration steps can be avoided.
[0071] The starting material of the process according to the invention, i.e. the first hydroprocessing catalyst, can thus be ground to produce catalyst fines. Suitable mills are known to the skilled person, and the choice of mill is not critical for the process according to the invention. Examples of suitable mills for the process are impact mills, ball mills or jet mills, preferably impact mills.
[0072] The starting material contains or is preferably ground to obtain particles with a median particle size D50 of less than 200 μm, preferably less than 100 μm, more preferably less than 50 μm, even more preferably less than 30 μm and preferably greater than 1 μm, more preferably greater than 2 μm and even more preferably greater than 4 μm. Taking into account that the catalyst fines are bonded together in a suitable extrudate, they preferably have a small particle size. Suitable extruders meet the requirements of minimum size, base crushing strength and maximum wear, which are usually set by the refiner. The particle size distribution is measured with a Malvern particle size analyzer. D50 is the corresponding particle size when the cumulative percentage reaches 50%. D50 is also called median particle diameter or median particle size.
[0073] D90 is the corresponding particle size when the cumulative percentage reaches 90%. In view of improved bonding and more stable extrudates, it is preferred that D90 is less than 500 μm, preferably less than 200 μm, more preferably less than 100 μm, and even more preferably less than 80 μm.
[0074] The particle size of the catalyst fines can be obtained by applying the correct settings in the mill used. Alternatively, a sieve can be used. Sometimes, the mill has a built-in sieve or air stream classifier to separate based on particle size.
[0075] In the method according to the present invention, if necessary, the first hydroprocessing catalyst is ground to form a catalyst fines, which are then mixed with a binder. If the first hydroprocessing catalyst consists of catalyst fines, grinding is not required, but it is generally preferred to also grind the catalyst fines to ensure that the mixture does not contain a large number of particles that are too large. Due to grinding, the shape or form of the first hydroprocessing catalyst provided is not critical for the method according to the present invention. The catalyst can be provided in the form of a full-length extrudate or in other shapes. The catalyst may also include damaged extrudates, or even catalyst fines, which may not even require grinding. The method according to the present invention therefore advantageously provides the possibility of utilizing damaged shaped catalysts or catalyst fines, which would otherwise be considered as waste materials.
[0076] In the process of preparing fresh catalyst, fresh catalyst fines are often formed as undesirable by-products. Fines can be formed in any process step in which the material is moved, but are usually formed during roasting, drying and forming processes. Fresh extrudates that do not meet the requirements in terms of size or shape can also be used in the method according to the present invention. Used catalyst extrudates are damaged due to mechanical damage during extrudate transportation, mechanical damage during reactor loading and unloading, mechanical wear of the catalyst and / or repeated harsh reaction conditions during hydroprocessing and / or regeneration, which destroy the required extrudate length. Used catalyst fines are also formed under these conditions.
[0077] In a preferred embodiment, the starting material comprises regenerated damaged or off-length extrudates and / or regenerated spent catalyst fines. These materials cannot be used by the refiner regardless of the catalytic activity of the material.
[0078] The catalyst fine powder is mixed with a binder to form a mixture. The binder may include any material capable of bonding the catalyst fine powder, and is generally selected from conventional inorganic oxides, such as alumina, silica, silica-alumina, alumina in which silica-alumina is dispersed, alumina coated with silica, magnesium oxide, zirconium oxide, boron oxide and titanium dioxide and mixtures of these oxides. The binder may also include a precursor of any of these conventional inorganic oxides, which may form an inorganic oxide when heat treated. For example, boehmite may be used as a binder, which is a precursor of γ-alumina. The method of the present invention does not necessarily need to reproduce the chemical composition of the first hydroprocessing catalyst. However, it is generally preferred to give priority to a binder similar to a binder material or carrier in the first hydroprocessing catalyst, i.e., a binder material also present in the catalyst fine powder, to produce a homogeneous mixture, and thus to produce a homogeneous resulting extrudate. In addition, the purpose of using a binder also already present in the catalyst fine powder is to produce an extrudate having chemical properties similar to those of the first hydroprocessing catalyst.
[0079] The mixture comprises at least 60% by weight of catalyst fines based on the dry weight of the mixture. In a preferred embodiment, the mixture comprises at least 70% by weight, preferably at least 80% by weight, more preferably at least 85% by weight, even more preferably at least 90% by weight, and most preferably at least 95% by weight of catalyst fines based on the dry weight of the mixture. A higher content of catalyst fines in the mixture means that the final catalyst prepared in the method according to the present invention contains a higher content of recycled catalyst material. In addition, a high content of catalyst fines in the final catalyst of the present invention also means that the final catalyst has a higher metal content because the binder does not contain metals. A higher metal content contributes to higher hydroprocessing activity.
[0080] In a further aspect, the invention provides a method of preparing a hydroprocessing catalyst, wherein the mixture comprises 100% catalyst fines based on the dry weight of the mixture. This means that the binder contains no dry material but may comprise a peptizing acid and / or water.
[0081] Binder and catalyst fine powder form a mixture that can be molded in an extruder. Suitable extrusion mixtures usually require some moisture. Therefore, the binder usually contains some water. The binder can also include a peptizing agent, such as an acid, for example nitric acid, citric acid, lactic acid or acetic acid. The mixture can further include an extrusion aid, such as clay, cellulose or a surfactant, which is usually present in an amount of 5 % by weight or less (based on the dry weight of the mixture).
[0082] Prior to forming or extrusion, the moisture content (LOI = loss on ignition) of the mixture can be adjusted, if necessary. An LOI that is too high may negatively affect the adhesion properties of the material, resulting in a brittle extrudate that breaks easily. An LOI that is too low will result in an extrudate that is brittle, too short, will contain cracks, the porosity will be reduced and / or the surface will not be smooth, which is undesirable. Adjusting the moisture content or LOI of the mixture is a matter within the common sense of the technician and may simply involve adding water or acid or controlled evaporation. Determining the appropriate moisture content or LOI for extrusion is a matter within the common sense and skill of the technician. The appropriate LOI for an extruded mixture is also equipment specific. In general, the moisture content should be approximately equal to the desired / target total pore volume of the mixture.
[0083] After extrusion, the shaped mixture is heat treated to dry the catalyst and, in the case of, for example, alumina, the phase of the binder material in the support changes to, for example, gamma, theta or eta-alumina. The shaped mixture is heat treated typically at a temperature in the range of 300° C. to 900° C., preferably between 400° C. and 800° C., more preferably between 450° C. and 650° C. The heat treatment can be carried out in two steps, for example a drying step between 80° C. and 150° C. and a heat treatment step at the above-mentioned elevated temperature, but can also be carried out in one step. Drying is preferably carried out to a volatile content in the range of 1 to 20 wt. % LOI.
[0084] In embodiments according to the invention, a high content of catalyst fines and thus a relatively low content of binder can advantageously be heat treated in one step.
[0085] The heat treated shaped mixture is then contacted with a restoring agent. The restoring agent comprises a complexing agent and may comprise an organic additive having a boiling point in the range of 80-500°C and a solubility in water of at least 5 g / l.
[0086] The result of contact with the restoring agent is indicated by a reduction in the crystalline fraction of the metal in the catalyst (expressed in wt %). In particular, the reduction in the crystalline fraction in the catalyst is measured by X-ray diffraction and is indicated by a reduction in the area of the β-CoMoO4 reflection at 26.4° 2θ of Cu-Ka radiation relative to a standard with a known amount of β-cobalt molybdate and / or a reduction in the β-NiMoO4 reflection at 26.58° 2θ.
[0087] Complexing agent and organic additive are incorporated into the catalyst in liquid form by impregnation. For complexing agent, this will usually mean that it is in a dissolved state. For organic additive, whether solvent is needed will depend on its property. If organic additive has enough mobility to enter the hole of catalyst when there is no solvent, solvent can be omitted. However, solvent will generally be used. Solvent is usually water, although other compounds may also be suitable, such as methanol, ethanol and other protic solvents, depending on the property of additive and / or complexing agent.
[0088] If the additive and / or complexing agent has been incorporated into the catalyst using a solvent, the catalyst can be dried after the impregnation step has been completed to remove at least part of the solvent, typically around 10% (weight percentage relative to the original weight of the compound), for example to produce a free-flowing powder. It is essential for the method according to the invention that any drying step is carried out in such a way that at least part of the additive and / or complexing agent remains on the catalyst. The catalyst is therefore not calcined. Therefore, the drying conditions to be applied depend to a large extent on the temperature at which the specific additive boils or decomposes. In the context of the present invention, the drying step should be carried out under such conditions that at least 50%, preferably 70%, more preferably 90% of the additive incorporated into the catalyst during the impregnation step remains in the catalyst after the drying step. Of course, it is preferred to keep as much additive as possible in the catalyst during the drying step, but evaporation of more volatile compounds during the drying step cannot always be avoided. The drying step can be carried out, for example, in air, under vacuum or in an inert gas. Generally, it is advantageous for the drying temperature to be below 220° C., although higher or lower temperatures may be required, depending on the nature of the additive. When the impregnation solution comprises water as solvent, drying is preferably carried out below 150° C., more preferably below 120° C., even more preferably below 100° C., most preferably below 90° C. The ageing step h) is followed by drying of the catalyst in a drying step i).
[0089] The complexing agent and the organic additive may be incorporated into the catalyst simultaneously or sequentially in no particular order. For reasons of efficiency, it is preferred that they are incorporated into the catalyst simultaneously.
[0090] Complexing agents are usually organic acids. In the context of this specification, organic acids are defined as compounds containing at least one carboxyl group (COOH). Organic acids preferably contain at least one carboxyl group and 1 to 20 carbon atoms (including the carbon atoms in the carboxyl group). Within this definition, various groups of complexing agents can be distinguished.
[0091] A first group of complexing agents preferred at this point in time is an organic acid selected from acetic acid, citric acid, malic acid, maleic acid, formic acid, glycolic acid, hydroxypropionic acid, hydroxybutyric acid, hydroxycaproic acid, lactic acid, tartaric acid, glyceric acid, gluconic acid, oxalic acid, malonic acid, polyacrylic acid and ascorbic acid. Within this group, citric acid and lactic acid are preferred. Lactic acid is particularly preferred.
[0092] The second group of complexing agents are N-containing acids, such as EDTA and CyDTA (1,2-cyclohexanediaminetetraacetic acid).
[0093] Organic additives that can be used in combination with complexing agents in the process according to the invention are organic compounds, i.e. compounds containing at least one carbon atom and at least one hydrogen atom, with a boiling point in the range of 80-500° C. and a solubility in water at room temperature (20° C.) (atmospheric pressure) of at least 5 g / l. The additives can be oxygen-containing or nitrogen-containing compounds.
[0094] The boiling point of the organic additive is preferably in the range of 100-400° C., more preferably 150-350° C. The boiling point of the additive is balanced based on the desire for the additive to remain on the catalyst during the preparation process (including optional drying and optional aging steps). During the use of the catalyst in the hydroprocessing process or during the sulfiding process, it may occur that at least some of the additive is removed from the catalyst. In the case where the organic additive does not have a boiling point but decomposes within a specified temperature range, the term boiling point is intended to be synonymous with the decomposition temperature.
[0095] The solubility of the additive at room temperature is at least 5 grams per liter, preferably at least 10 grams. It is noted that the solubility requirement for the additive has a twofold basis. Firstly, compounds that meet this solubility requirement are convenient to use in the impregnation solution. In addition, it seems that compounds that meet these solubility requirements interact in some way with the metal components present in the catalyst, leading to an increased activity of the final product. Within this definition, various groups of additives can be distinguished.
[0096] The first group of additives is an organic compound group comprising at least two oxygen atoms and 2-20 carbon atoms, preferably 2-10 carbon atoms, and compounds consisting of these compounds. Organic compounds selected from compounds comprising at least two oxygen-containing moieties (such as carboxyl, carbonyl or hydroxyl moieties) and 2-10 carbon atoms and compounds consisting of these compounds are preferred. Examples of suitable compounds include butanediol, methylglyoxal, glycolaldehyde and acetaldehyde alcohol.
[0097] The second group of additives preferred at this time point is an additive group selected from compounds containing at least two hydroxyls and 2-10 carbon atoms per molecule and (poly) ethers of these compounds. Suitable compounds in this group include fatty alcohols, such as ethylene glycol, propylene glycol, glycerine, trimethylolethane, trimethylolpropane, etc. The ethers of these compounds include diethylene glycol, dipropylene glycol, trimethylene glycol, triethylene glycol, tributylene glycol, tetraethylene glycol, tetrapentanediol. This range can be extrapolated to include polyethers, such as polyethylene glycol. Other ethers suitable for the present invention include ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monopropyl ether and diethylene glycol monobutyl ether. Among these, ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, propylene glycol, dipropylene glycol and polyethylene glycol with a molecular weight between 200 and 600 are preferred. Another group of compounds containing at least two hydroxyls and 2-10 carbon atoms per molecule is sugar. Preferred sugars include monosaccharides such as glucose and fructose. Ethers thereof include disaccharides such as lactose, maltose and sucrose. Polyethers of these compounds include polysaccharides. Organic compounds of this group are preferably substantially saturated, as evidenced by an iodine value of less than 60, preferably less than 20.
[0098] A third group of organic additives suitable for use in the present invention are those compounds comprising at least one covalently bonded nitrogen atom and at least one carbonyl moiety. Organic compounds of this type preferably comprise at least two carbonyl moieties. Preferably at least one carbonyl moiety is present in a carboxyl group. It is further preferred that at least one nitrogen atom is covalently bonded to at least two carbon atoms. Preferred organic compounds satisfy formula (I) or (II)
[0099] (R1R2)N-R3-N(R1'R2') (I)
[0100] N(R1R2R1') (II)
[0101] Wherein R1, R2, R1' and R2' are independently selected from alkyl, alkenyl and allyl, and up to 10 carbon atoms are optionally substituted by one or more groups selected from carbonyl, carboxyl, ester, ether, amino or amido. R3 is an alkylene group with up to 10 carbon atoms, which may be interrupted by -O- or -NR4-. R4 is selected from the same group as indicated by R1 above. R3 alkylene may be substituted by one or more groups selected from carbonyl, carboxyl, ester, ether, amino or amido. As stated above, it is important that the organic compound of formula (I) or (II) contains at least one carbonyl moiety.
[0102] Preferably, at least two of R1, R2, R1' and R2' (formula (I)) and at least two of R1, R2 and R1' (formula (II)) have the formula -R5-COOX, wherein R5 is an alkylene group having 1-4 carbon atoms and X is hydrogen or another cation, such as an ammonium, sodium, potassium and / or lithium cation. If X is a polyvalent cation, one X may be attached to two or more -R5-COO groups. Typical examples of compounds of formula (I) are ethylenediamine(tetra)acetic acid (EDTA), hydroxy-ethylenediaminetriacetic acid and diethylenetriaminepentaacetic acid. Typical examples of compounds of formula (II) are nitrilotriacetic acid (NTA). For solubility reasons, salts of these compounds may be preferred.
[0103] It is to be noted that the description of the organic additive mentioned above covers various acidic components. In the context of the present invention, the combination of organic acid and organic additive is discussed, which means that (at least) two different compounds are used, one of which is an acid and the other of which meets the solubility and boiling point requirements for the organic additive. The latter compound may or may not be acidic.
[0104] Furthermore, it is to be noted that the above-mentioned description of solvents covers various compounds that also meet the description of organic additives. In the context of the present invention, a combination of solvent and organic additive is discussed, which means that (at least) two different compounds are used, one of which is a solvent and the other of which meets the solubility and boiling point requirements for the organic additive. The latter compound may or may not be acidic.
[0105] From an environmental point of view, it is preferred to use an organic additive that is substantially free of sulfur. Further, sulfur-containing additives are generally unstable with respect to oxygen. Therefore, if a sulfur-containing additive is to be used, all subsequent process steps will have to be carried out under an inert atmosphere. Moreover, for this reason, it is preferred to use a sulfur-free additive. This applies to both acids and organic additives. Single compounds as well as combinations of compounds can be used as organic additives.
[0106] If complexing agent and additive are used simultaneously, the total amount of complexing agent and additive used in the method according to the present invention is at least 0.01 mole, preferably at least 0.05 mole, more preferably at least 0.1 mole of total complexing agent and additive per mole of total Group VI and Group VIII metal. There is no specific upper limit to the total amount of complexing agent and additive added, because there is no problem in providing in excess. The technician can find the optimal amount required to achieve the best recovery effect. Suitable molar ratio can be at most 3, preferably at most 2.
[0107] If an organic acid is used as a complexing agent, the amount of acid is generally between 0.01 and 1 mole per mole of total Group VI and Group VIII metals, preferably between 0.05 and 0.5 mole per mole of total Group VI and Group VIII metals. Preferably, at least 5 wt. %, more preferably at least 7 wt. %, even more preferably at least 10 wt. % and most preferably at least 15 wt. % of organic acid is used relative to the weight of the catalyst. Where an organic additive is also used, preferably at least 5 wt. %, more preferably at least 10 wt. % of organic acid is used relative to the weight of the catalyst, and at least 5 wt. %, preferably at least 10 wt. % of organic additive is used relative to the weight of the catalyst.
[0108] The amount of organic additive is generally between 0.1 and 2.5 moles per mole of total Group VI and Group VIII metals, preferably between 0.15 and 1 mole per mole of total Group VI and Group VIII metals, more preferably between 0.2 and 1 mole per mole of total Group VI and Group VIII metals.
[0109] If the restoring agent comprises both a complexing agent and an organic additive, the molar ratio between the complexing agent and the additive is generally 0.01-10:1, preferably 0.1-5:1, more preferably 0.15-3:1.
[0110] Generally speaking, if the total amount of restoring agent added is too low, no beneficial restoring effect will be obtained. As will be clear to those skilled in the art, the exact amount of restoring agent to be used in a particular case will depend on a variety of parameters, including the metal content of the catalyst, the pore volume and pore size distribution of the catalyst, the nature of the restoring agent, the solvent to be used in the impregnation solution, the impregnation conditions, etc. Taking into account the above-mentioned variables, it is well within the ability of those skilled in the art to determine the optimal amount of restoring agent to be used in each specific case.
[0111] In a preferred embodiment of the method of the present invention, after the incorporation of the restoring agent, the heat-treated shaped mixture is subjected to an aging step. The aging step is carried out while the catalyst is still wet, i.e. before the solvent is removed from the catalyst. The aging time applied in the aging step is a function of temperature. Generally, the aging time is shortened with an increase in the aging temperature. The aging step usually takes at least 15 minutes. After a certain period of time, for example, after more than 48 hours, no additional activity increase is observed. If the aging step is carried out at a temperature between 0°C and 50°C, the aging time is usually at least 1 hour, can be at least 2 hours, or can be at least 6 hours. If the aging step is carried out at a temperature above 50°C, the aging time is usually at least 0.5 hours, can be at least 1 hour, or can be at least 2 hours. The aging step can also be carried out under hydrothermal conditions at a temperature above 100°C for a period of more than 15 minutes. The aging step can also be carried out by heating the catalyst with microwaves or induction heating.
[0112] Surprisingly, it has been found that good results (high HDS and HDN activity) can be obtained even with relatively short aging times. An aging time of 18 hours, which is often used in practice, does not produce significantly better results than aging for 1 hour. Therefore, it is preferred that aging is carried out at a temperature between 20°C and 100°C, preferably between 30°C and 80°C, and preferably for a duration of less than 18 hours, preferably less than 15, 10, 7, 4 hours or even less than 2 hours. In a preferred embodiment, aging is carried out for a time between 0.5 and 2 hours, preferably between 0.5 and 1 hour, and between 30°C and 80°C.
[0113] Preferably, the catalyst composition is aged for a time sufficient to reduce the crystalline fraction to below 5 wt.-%, more preferably below 2.5 wt.-%. It has further been found that the aging time can be greatly shortened and / or significantly better results can be obtained if, in the process according to the invention, the concentration of the complexing agent is at least 5 wt.-%, preferably at least 7 wt.-%, most preferably at least 10 wt.-% (relative to the total weight of the catalyst).
[0114] According to an embodiment of the present invention, the recovered mixture is suitable for transportation in its wet state. Drying is not required for transportation. Therefore, drying can be carried out in situ during the hydroprocessing process. However, in practice, for example, for reasons of transportation and storage, it is often preferred to provide a dried catalyst.
[0115] In a further aspect according to the present invention, the method further comprises the step of contacting the heat-treated shaped mixture with a solution containing a Group VI and / or Group VIII metal, wherein the step can be performed before, during or after the heat-treated shaped mixture is contacted with a restoring agent. In a preferred embodiment, the heat-treated shaped mixture is contacted with a solution containing both a restoring agent and a Group VI and / or Group VIII metal.
[0116] It has been found that when the amount of catalyst fines in the catalyst is high, good activity can be obtained even without adding metal in the recovery step. For example, when the amount of catalyst fines in the catalyst is at least 80%, preferably at least 85%, more preferably at least 90%, and most preferably at least 95%, the HDS activity of such catalyst (under conditions as described in the Examples below) relative to the HDS of fresh commercial KF757 can be at least 50%, preferably at least 55%, more preferably at least 60%, or even at least 65%, even without adding metal, but will be even higher than when metal is also added.
[0117] In another aspect of the invention, Group VI and / or Group VIII metals may be added to the mixture prior to shaping the mixture. After shaping, the shaped mixture may then be subjected to a heat treatment step and / or a recovery step (ie, contacting the heat treated shaped mixture with a recovery agent).
[0118] When the catalyst fines are mixed with a binder to form a mixture that can be molded and heat treated, the metal concentration is diluted. Since the activity is related to the amount of metal in the catalyst material, the dilution of the first hydroprocessing catalyst fines with a binder also reduces the activity of the final hydroprocessing catalyst, which will therefore also be lower than the expected activity of the fresh catalyst. The object of the present invention is to restore the activity of the catalyst material as much as possible, preferably to achieve at least 60% of the activity of the corresponding fresh hydroprocessing catalyst, preferably at least 75%, more preferably at least 85%, even more preferably at least 90%. Therefore, it is advantageous to impregnate the heat treated molded mixture with a solution containing Group VI and / or Group VIII metals.
[0119] The solution may preferably contain metals in amounts and ratios to each other to restore the metal content of the first hydroprocessing catalyst. In other words, when the mixture contains 80% by weight catalyst fines on a dry weight basis, the metal concentration in the shaped, heat-treated mixture will be 80% compared to the metal concentration in the first hydroprocessing catalyst. In a preferred embodiment, the impregnation solution contains an amount of metal such that, after contact with the solution containing Group VI and / or Group VIII metals, the heat-treated shaped mixture contains a metal concentration of at least 90% by weight, preferably at least 95% by weight, and more preferably at least 98% by weight of the metal concentration in the first hydroprocessing catalyst.
[0120] According to another aspect of the invention, the impregnation solution comprises an amount of metal such that after contacting, the heat treated shaped mixture comprises a metal concentration greater than 100 wt % of the metal concentration in the first hydroprocessing catalyst. This may be advantageous for improved catalyst activity recovery.
[0121] According to another aspect of the invention, a Group VI or Group VIII metal different from the metal present in the first hydroprocessing catalyst may be used in the solution, only one metal may be used, or different ratios of the metals may be used. Changing the nature or ratio of the metals may affect the activity or selectivity of the final catalyst in the hydroprocessing process.
[0122] According to another aspect, the present invention relates to a hydroprocessing catalyst obtainable by the process according to the present invention. This hydroprocessing catalyst is characterized by a total pore volume of 0.2 to 1.0 mL / g, preferably 0.3 to 0.6 mL / g. The hydroprocessing catalyst has a typical macropore volume of 0.005-0.3 mL / g, preferably a macropore volume of less than 0.06 mL / g. In this context, pores with a diameter greater than 100 nm are considered macropores, and a surface area of 100-300 m 2 / g.
[0123] The hydroprocessing catalyst obtained or obtainable by the method of the present invention can be subjected to a drying step before it is used for the hydroprocessing of hydrocarbon feedstock, and can be subjected to a sulfurization step, but as explained before, this is not necessary. If it is decided that the catalyst is sulfurized before use, one of the methods known in the art can be adopted to carry out. For example, the catalyst can be contacted with an inorganic or organic sulfur compound (such as hydrogen sulfide, elemental sulfur or organic polysulfide), or the catalyst is sulfurized by contacting it with the hydrocarbon feedstock to which the sulfur compound has been added. This will all be catalyst sulfurization or presulfurization known to the technician.
[0124] This catalyst can be used for the hydroprocessing of many kinds of raw materials.Any raw material comprising hydrocarbon is suitable for one or more of hydrodesulfurization, hydrodenitrogenation and hydrodearomatization.The example of suitable raw material includes petroleum fraction, the fraction produced by coal or the hydrocarbon produced by natural gas, optionally as mixture, or also from the hydrocarbon fraction produced by biomass, and includes but not limited to gasoline, gas oil, vacuum gas oil, middle distillate, naphtha, atmospheric residue, vacuum residue, atmospheric distillate, vacuum distillate, heavy fuel oil, oils, wax and paraffin, waste oil, deasphalted residue or crude oil, originate from the raw material of heat or catalytic conversion process, lignocellulose raw material, or more generally, raw material, organic waste raw material, plant (waste) raw material produced by biomass alone or as mixture.Processed raw material (and particularly those mentioned above) usually contains heteroatoms, such as sulphur, oxygen and nitrogen, and for heavy raw materials, they also contain metal usually. The catalyst is particularly suitable for ultra-deep hydrodesulfurization, i.e. hydrodesulfurization to a product sulfur content of less than 200 ppm, more particularly to a product sulfur content of less than 50 ppm. Conventional process conditions may be applied here, such as a temperature in the range of 250° C. to 450° C., a pressure in the range of 5 to 250 bar, a space velocity in the range of 0.1 to 10 h-1 and a H2 / oil ratio in the range of 50 to 2000 Nl / l.
[0125] The present invention will be further illustrated using the following examples.
[0126] Definition and Methodology
[0127] The weight db is a dry basis weight after drying at 600°C for 1.5 hours.
[0128] LOI is the loss on ignition, ie the weight loss after treatment at 600°C for 1.5 hours.
[0129] CA is citric acid, DEG is diethylene glycol, LA is lactic acid
[0130] SA is the surface area measured by the BET method with nitrogen on a Micromeritics GEMINI VII analyzer according to ASTM D3663-03 and ASTM D4365-95. Unless otherwise stated, the samples were pre-treated by drying at 450°C for 1 hour.
[0131] For samples dispersed in water, the particle size distribution (and particle size) is measured by laser scattering using a Malvern MasterSizer 3000Hydro-LV dispersion device. D50 is the particle size when the cumulative percentage in the measured particle size distribution reaches 50%. D50 is also called the median particle diameter or median particle size. D90 is the corresponding particle size when the cumulative percentage reaches 90%.
[0132] The pore volume Hg21 (PV Hg21) is the pore volume measured by mercury intrusion porosimetry (AutoPore IV 9520) in the pore diameter range of 4.2 to 8000 nm.
[0133] The support is a catalyst support which has been extruded after drying and heat treatment. The final catalyst is a support which has been impregnated with a restoring agent and / or a metal and optionally dried.
[0134] Side crushing strength (SCS) was analyzed with a Vinci SCS tester and performed on 40 particles. The average SCS was determined as force (lbs) per unit length (mm).
[0135] Pore volume water: The pores of the calcined (600°C, 1 h) sample of particles are filled with water added in a controlled manner. The endpoint of this titration is indicated by a sudden change in the fluidity of the sample.
[0136] X-ray fluorescence spectroscopy (XRF) was performed with a PANalytical Axios or Zetium. Unless otherwise stated, samples were pretreated by drying at 450°C for 1 hour.
[0137] XRD measurements were performed using a Bruker D4 Endeavor XRD apparatus.
[0138] The weight percent of catalyst fines is defined as the weight of catalyst fines (db) to the final dry basis weight of the support (db).
[0139] Preparation of catalyst fine powder
[0140] A batch of commercially used hydroprocessing catalyst (KF-757) containing cobalt and molybdenum (CoMo) was regenerated by Eurecat SA of France. During this regeneration, a portion of dust and too short extrudates were screened out. This portion of the regenerated catalyst was collected and brought to the laboratory for catalyst preparation. This portion of the regenerated catalyst was ground in an impact mill to obtain a catalyst fine powder with the following particle size distribution: D50 = 17.6 μm, and 99.8% of the volume was composed of particles with a particle size diameter less than 64.6 μm. The catalyst fine powder contained 4% by weight of CoO, 24% by weight of MoO3 and 2% by weight of P2O5 supported on γ-Al2O3.
[0141] Preparation of Support C1 (80 wt. % Catalyst Fine Powder)
[0142] Use Eirich mixer to carry out three-step mixing scheme.First, 10334g of HNO3 aqueous solution (1.8 weight % relative to the gross weight of water) is added to the mixture of 4393g of spray-dried aluminum oxide and 6645g of catalyst fine powder, while mixing at 200rpm.Then continue mixing at 800rpm until densification is observed by power absorption peak.Then add 3629g of catalyst fine powder and continue mixing until densification is observed again by power absorption peak.In the last step, 3069g of catalyst fine powder is added together with 48g of modified cellulose extrusion aid (Walocell CMC), and continue mixing at 600rpm for a set time of 5 minutes.A mixture containing 80 weight % of catalyst fine powder based on dry mixture is obtained like this.This mixture is used for extrusion.
[0143] The extrusion was carried out using a ZSK-32 extruder. The extrudate was dried in a drying chamber at 120°C for a minimum of 3 hours and calcined at 450°C for 1 h. The resulting extrudate is further referred to herein as support. The properties of support C1 are listed in Table 1.
[0144] Table 1: Properties of Carrier C1 (80% regenerated fines)
[0145] Pore volume Hg21 (mL / g) 0.44 Median pore size (nm) 11.8 <![CDATA[Surface area (m 2 / g)]]> 213 Side crushing strength (lbs / mm) 5.2
[0146] Reference Catalyst RC1
[0147] Freshly prepared batches of commercial hydroprocessing catalyst KF-780 were used as reference catalysts to test their hydrodesulfurization (HDS) and hydrodenitrogenation (HDN) activities during hydroprocessing. Reference catalyst RC1 contained 4 wt% CoO, 24 wt% MoO3 and 2 wt% P2O5 supported on γ-Al2O3.
[0148] Example 1-3: Impregnation of Carrier C1 with CA and DEG
[0149] In each example, support C1 was impregnated with 95% of the pore volume.
[0150] Example 1 : The support C1 was impregnated with an organic solution containing citric acid (CA) and diethylene glycol (DEG) to finally reach 5.5 wt % CA and 11 wt % DEG on the final catalyst based on the dry weight of the final catalyst. The required amount of solution 12.60 mL (consisting of 2.96 g CA (50 wt % solution in water) + 3.13 g DEG + 7.42 g water) was poured on the support (25.66 grams dry basis (g db)) while mixing.
[0151] Example 2-3: Following the same procedure and equal amounts as in Example 1. A solution consisting of 2.39 g CA (50 wt% solution in water) + 2.53 DEG + 5.99 g water was poured on top of 20.6 g db support C1 while mixing so that there were 5.5 wt% CA and 11 wt% DEG on the final dry catalyst.
[0152] All impregnated extrudates of Examples 1-3 and Examples 4-12 described below were aged at a temperature of 60°C and dried at a product temperature T=80°C for the times indicated in Table 5.
[0153] Example 4-6: Impregnation of Support C1 with CA, DEG and Metals
[0154] Example 4 : The support material C1 was impregnated with a solution containing CA, DEG and Co, Mo and P metals to reach 24 wt% MoO3, 4 wt% CoO and 2 wt% P2O5 with 5 wt% CA and 10 wt% DEG based on the dry weight of the final catalyst. The CoMoP solution was prepared by adding cobalt hydroxycarbonate, molybdenum oxide and phosphoric acid as raw materials to water. 25.66 g of the dry basis support material C1 was impregnated with 12.60 ml of a solution consisting of 6.12 g metal sol + 2.96 g CA (50 wt% solution in water) + 3.13 g DEG + 3.44 g water. The CA-DEG-CoMoP solution was poured over the extrudates while stirring.
[0155] Embodiment 5-6 : Following the same procedure as in Example 4, equivalent quantities and target final composition: 10.71 mL of solution (consisting of 4.94 g metal solution + 2.39 g CA (50 wt% solution in water) + 2.53 g DEG + 2.78 g water) was poured over 20.58 g db support C1 while stirring.
[0156] Examples 7-9: Impregnation of Carrier C1 with LA
[0157] Embodiment 7: The support C1 was impregnated with a solution containing lactic acid to give 22 wt% lactic acid on the final catalyst. 12.6 mL of a solution consisting of 7.96 g lactic acid (88% lactic acid content) + 6.00 g water was poured on 25.7 g db of support C1 while stirring.
[0158] Embodiment 8-9: The same procedure as in Example 7 was followed: 10.17 mL of a solution (consisting of 6.43 g lactic acid + 4.84 g water) were poured on 20.6 g db of support C1 so that there were 22 wt% lactic acid on the final catalyst, based on its dry weight.
[0159] Examples 10-12: Impregnation of Support C1 with LA and Metals
[0160] Embodiment 10: The support C1 is impregnated with a solution containing lactic acid and Co, Mo and P metals. The final target composition is 24 wt% MoO3, 4 wt% CoO and 2 wt% P2O5 and 20 wt% lactic acid. The CoMoP solution is prepared using cobalt hydroxycarbonate, molybdenum oxide and phosphoric acid as raw materials. The raw materials are combined in water. 25.76 g db (water pore volume = 0.51 ml / g) of the support material C1 is impregnated with 12.60 ml (95% pore volume) of a solution consisting of 6.12 g metal solution + 7.91 g lactic acid (88%) + 2.02 g water. The solution of the metal + lactic acid solution is heated until a clear solution is obtained and poured over the extrudates while stirring.
[0161] Examples 11-12 : The same procedure and equivalent quantities were followed as in Example 10. 20.7 g of db support C1 were impregnated with 4.94 g metal solution + 6.43 g lactic acid (88%) + 1.63 g water.
[0162] Comparative Example CE1: Impregnation of Support C1 with Metals without Restoration Agent
[0163] 20.7 g db of support C1 was impregnated with 10.15 ml (95% pore volume) solution of Co, Mo and P metals to reach a target final composition of 24 wt% MoO3, 4 wt% CoO and 2 wt% P2O5. The CoMoP solution was prepared by adding cobalt hydroxycarbonate, molybdenum oxide and phosphoric acid as raw materials to water and heating until a clear solution was obtained. The CoMoP solution was poured over the extrudates while stirring. The impregnated extrudates were aged as shown in Table 5.
[0164] XRD measurement
[0165] All XRD measurements were performed using a Bruker D4 Endeavor XRD device. The effect of impregnation on the reduction of the crystalline phase indicates a redistribution of the active phase. X-ray diffraction was used to quantify the amount of crystalline β-CoMoO4 present on the support C1 and on the impregnated catalysts according to Examples 1-12. The crystalline fraction of β-CoMoO4 in the sample (expressed as weight percentage) was determined from the X-ray diffraction pattern by evaluating the net peak area of the strongest reflection of β-cobalt molybdate at about 26.4° 2θ of Cu-ka radiation relative to a standard with a known amount of β-cobalt molybdate.
[0166] For the samples impregnated with CA+DEG (with and without metal), the relative amount of β-CoMoO4 ranges from 2.7 to 3.5 wt. %, indicating a reduction in crystalline CoMoO4 after impregnation on support C1 (β-CoMoO4=5.6). For the samples impregnated with lactic acid (containing 20% metal and without metal), the relative amount of CoMoO4 ranges from 0.7 to 1.8 %, indicating a stronger reduction in β-CoMoO4 after impregnation on the support (β-CoMoO4=5.6%). For all examples, the reduction in the crystalline oxide phase indicates an acceptable redistribution of the active phase. The results of the XRD measurements are listed in Table 2.
[0167] Table 2. Quantitative estimation of the β-CoMoO4 phase in the catalysts prepared according to Examples 1-12 and in the support C1 by XRD.
[0168] Example Final Catalyst <![CDATA[β-CoMoO4]]> - Carrier only 5.6 1 5.5 wt% CA + 11 wt% DEG 2.7 2 5.5 wt% CA + 11 wt% DEG 3.3 3 5.5 wt% CA + 11 wt% DEG 3.2 4 Added metal + 5 wt% CA + 10 wt% DEG 3.3 5 Added metal + 5 wt% CA + 10 wt% DEG 3.5 6 Added metal + 5 wt% CA + 10 wt% DEG 3.5 7 Lactic acid (22 wt%) 0.7 8 Lactic acid (22 wt%) 0.8 9 Lactic acid (22 wt%) 0.9 10 Added metal + lactic acid (20 wt%) 1.1 11 Added metal + lactic acid (20 wt%) 1.5 12 Added metal + lactic acid (20 wt%) 1.8 CE1 Only added metals 5.6
[0169] Activity measurements of the catalysts of Examples 1-12 and reference catalyst RC1
[0170] Catalysts from Examples 1-12 and reference catalyst RC1 were tested for hydrodesulfurization (HDS) and hydrodenitrogenation (HDN) activities under medium pressure ULSD conditions as shown in Table 3. The samples were tested at a compacted loading CBD (compacted bulk density) equal to their respective references (fresh CoMo commercial catalyst according to Reference Example 1).
[0171] Table 3. Precuring and testing conditions
[0172]
[0173] LHSV = Liquid Hourly Space Velocity (1 / h) **H2 / Oil: Standard liters of H2 / liter of oil, SPF = Spiked Stock Diesel Stock has the properties shown in Table 4
[0174] Table 4. Raw material properties
[0175] nitrogen mg / kg 178 Sulfur (XRF) mg / kg 8890 Density at 60F g / ml 0.8566 1% by weight ℃ 99 5 wt% ℃ 172 10% by weight ℃ 205 50% by weight ℃ 291 95% by weight ℃ 377 99% by weight ℃ 434
[0176] The reference catalyst RC1 is set to 100% by definition. All examples are compared and calculated relative to this reference catalyst. The test results of the catalysts of Examples 1-12 and the fresh reference catalyst RC1 are listed in Table 5.
[0177] Table 5: Relative volumetric activities of catalysts based on support C1.
[0178]
[0179] The test results (HDS and / or HDN volume activity) of the catalyst according to the invention and the fresh commercial catalyst RC1 show that the catalyst restored with CA+DEG can restore up to 57-85% of the HDS activity of the commercial catalyst, and the restoration with lactic acid can restore up to 60-90% of the HDS activity of the commercial catalyst. Aging and / or drying have no significant effect on the activity. Both LA and CA+DEG can be used as restoration agents.
[0180] Preparation of fine powder of catalyst with carrier C2-C6
[0181] A batch of commercially used hydroprocessing catalyst (KF-780) containing cobalt and molybdenum (CoMo) was regenerated and catalyst fines of support C1 were prepared as described above to obtain catalyst fines having a particle size distribution of D50 = 14.1 μm and 100% of the volume consisting of particles with a particle size diameter of less than 64.6 μm. The catalyst fines contained 4.1 wt% CoO, 20.6 wt% MoO3 and 2.8 wt% P2O5 supported on γ-Al2O3.
[0182] Preparation of supports C2-C6 (95 wt. % catalyst fines) with different binders
[0183] The mixing protocol was carried out using an Eirich mixer. 1194 g of an aqueous HNO3 solution (0.47 wt. % relative to the total weight of water) was added to a mixture of 137.3 g of a binder (spray-dried alumina), 2000 g of catalyst fines and 6 g of an extrusion aid. This gave a mixture containing 95 wt. % of catalyst fines based on the dry mixture.
[0184] Extrusion was performed using a ZSK-32 extruder. The extrudate was dried in a drying chamber at 120° C. for a minimum of 3 hours and calcined at 450° C.-650° C. for 1 h. The resulting extrudate is further referred to herein as carrier C2.
[0185] With carrier C7 and WO2012021386A1 Figure 1 Compared to the PSD of the prior art support of Example 1 (made of 30 wt. % catalyst fines and alumina powder) shown in FIG, the pore size distribution PSD of support C2 is shown in FIG. Figure 1 (Cumulative intrusion of Hg21, unit: ml / g PV). Figure 1 It is shown that the volume of the macropores in the carriers C2 and C7 of the present invention is much smaller than that in the prior art: the size exceeds The cumulative pore volume in the macropores of C2 is about 0.1 and 0.06 ml / gr, respectively, compared to about 0.16 ml / gr in the prior art. The carrier of the present invention has a significantly lower macropore volume. As shown in Examples 13 and 17, the catalyst prepared from carrier C2 has a very good activity; even up to 100% compared to the commercial catalyst (RC2).
[0186] Carriers C3-C6 were produced with different binders, except that no additional HNO3 was added. Silica, aluminum acetate, Acti-gel were used in the extrusion of the catalyst fines. R (a magnesium aluminum silicate) or a solution mixture of aluminum nitrate binder. The properties of the carrier are listed in Table 6 middle.
[0187] Table 6: Properties of Carriers C2-C6 (95% Regeneration Fines)
[0188]
[0189] Reference Catalyst RC2
[0190] Freshly prepared batches of commercial hydroprocessing catalyst KF-780 were used as reference catalysts to test their hydrodesulfurization (HDS) and hydrodenitrogenation (HDN) activities during hydroprocessing. Reference catalyst RC2 contained 4.4 wt% CoO, 21 wt% MoO3 and 3.2 wt% P2O5 supported on γ-Al2O3.
[0191] Examples 13-16: Carriers C2-C6 impregnated with CA, DEG, Co, Mo and P
[0192] Support C2 was impregnated with a solution containing CA, DEG and Co, Mo and P metals to achieve a target final composition of 21 wt% MoO3, 4.4 wt% CoO and 3.2 wt% P2O5 with organic citric acid (CA) and diethylene glycol (DEG), with 10 wt% CA and 11 wt% DEG on the final catalyst based on the dry weight of the final catalyst. The CoMoP solution was prepared by adding cobalt hydroxycarbonate, molybdenum oxide and phosphoric acid as raw materials to water. Similar preparations were performed using supports C3-C6.
[0193] 103.6 g of db support C2 (binder: spray-dried alumina) was impregnated with 50.37 ml of a solution consisting of 3.81 g metal sol + 0.71 g H3PO4 (75 wt% solution in water) + 21.30 CA (50 wt% solution in water) + 11.7 g DEG + 20.04 g water. The CA-DEG-CoMoP solution was poured over the extrudates while stirring. The impregnated extrudates were aged at 60°C for 45 minutes and dried at product T 80°C for 1 hour.
[0194] The hydrodesulfurization (HDS) and hydrodenitrogenation (HDN) activities of these catalysts were tested under the medium pressure ultra low sulfur diesel conditions described in Tables 3 and 4 and at a temperature of T = 335 ° C and a pressure of P = 45 bar and compared with the reference catalyst RC2. The activity of the reference catalyst RC2 was set to 100% by definition. The catalysts were compared with this reference catalyst RC2 and the relative activities were calculated in the following Table 7.
[0195] Example 17: Support C2 impregnated with CA, DEG and higher content of CoMoP
[0196] Example 13 was repeated, except that support C2 was impregnated to achieve a higher metal content, reaching a target final composition of 23.5 wt% MoO3, 5 wt% CoO and 5 wt% P2O5. 103.6 g of support C2 of db were impregnated with 48 ml of a solution consisting of 17.9 g of a metal solution containing MoO3, CoO and 3.33 g H3PO4 (75 wt% solution in water) + 22 g CA (50 wt% solution in water) + 12 g DEG + 6.76 g water. The catalyst was tested as described in Example 13; the results are in Table 7. Example 17 shows that the activity can be restored, even to nearly 100% of the fresh commercial catalyst.
[0197] Table 7 Activity measurements of Examples 13-17
[0198] Example Carrier (binder) RVA-HDS(ppm S) RVA-HDN(ppm N) RC2 not applicable 100 100 13 C2 78 79 14 C3 79 82 15 C4 76 75 16 C5 76 77 17 C2 101 96
[0199] Preparation of Support C7 with Aluminum Acetate (98 wt. % Catalyst Fines)
[0200] A batch of commercially used hydroprocessing catalyst (KF-780) containing cobalt and molybdenum (CoMo) was regenerated and catalyst fines of support C1 were prepared as described above to obtain catalyst fines having a particle size distribution of D50 = 13.4 μm and 100% of the volume consisting of particles with a particle size diameter of less than 64.6 μm. The catalyst fines contained 4.1 wt% CoO, 22.5 wt% MoO3 and 2.2 wt% P2O5 supported on γ-Al2O3.
[0201] The mixing scheme was carried out using an Eirich mixer. 127.2 g of aluminum acetate, 2076 g of catalyst fines and 5.9 g of extrusion aid were mixed with 1058 g of water. This gave a mixture containing 98% by weight of catalyst fines based on the dry mixture. Extrusion was carried out using a ZSK-32 extruder. The extrudate was dried in a drying cabinet at 120° C. for a minimum of 3 hours and calcined at 450° C.-650° C. for 1 h. The properties of the carrier C7 are listed in Table 8 middle. Figure 1 The pore size distribution PSD (cumulative intrusion of Hg21, in ml / g PV) of support C7 is shown in FIG.
[0202] Preparation of support C8 with alumina and citric acid (80 wt. % catalyst fines)
[0203] A catalyst fine powder of carrier C8 was prepared as described above, with a particle size distribution D50 = 22.7 μm, and 98.8% by volume consisting of particles with a particle size diameter less than 64.6 μm. The catalyst fine powder contained 3.9 wt% CoO, 17.7 wt% MoO3 and 1.7 wt% P2O5 supported on γ-Al2O3.
[0204] The mixing scheme was carried out using an Eirich mixer. 1296 g of aqueous citric acid solution (6.2 wt % relative to the total weight of water) was added to a mixture of 549 g of spray-dried alumina, 1727 g of catalyst fines and 6 g of extrusion aid. This resulted in a mixture containing 80 wt % of catalyst fines. Extrusion was carried out using a ZSK-32 extruder. The extrudate was dried in a drying chamber at 120° C. for a minimum of 3 hours and calcined at 450° C. for 1 h. The properties of carrier C8 are listed in Table 8.
[0205] Table 8: Properties of carriers C7 and C8
[0206] C7 C8 Recycled fine powder (wt%) 98 80 Pore volume Hg21 (mL / g) 0.41 0.52 <![CDATA[Surface area (m 2 / g)]]> 169 250 Side crushing strength (lbs / mm) 5.5 2.8
Claims
1. A method for preparing a hydroprocessing catalyst, the method comprising a) providing a first hydroprocessing catalyst comprising a Group VI metal and a Group VIII metal selected from the group consisting of fresh catalyst, regenerated catalyst, restored catalyst, fresh, regenerated or restored catalyst fines, or mixtures thereof; b) grinding the first hydroprocessing catalyst to form catalyst fines, unless the first hydroprocessing catalyst already consists of fresh, regenerated or rejuvenated catalyst fines or mixtures thereof; c) mixing the catalyst fines with at least a binder to form a mixture; wherein optionally the mixing and grinding are at least partially combined, and wherein optionally during the mixing a first hydroprocessing catalyst consisting of fresh, regenerated or rejuvenated catalyst fines is added after grinding, wherein the mixture comprises at least 60 wt% catalyst fines based on the dry weight of the mixture; d) shaping the mixture to form a shaped mixture; e) heat treating the shaped mixture; f) contacting the heat treated molding mixture with a restoring agent.
2. The method according to claim 1, wherein the method further comprises a step g) of contacting the heat-treated shaped mixture with a solution comprising a Group VI and / or Group VIII metal and optionally a phosphor compound, wherein the step g) can be performed before, during or after step f), or wherein the Group VI and / or Group VIII metal is added to the mixture before shaping the mixture.
3. A process according to claim 2, wherein the solution comprises an amount of Group VI and / or Group VIII metal such that, after contacting, the heat-treated shaped mixture comprises a metal concentration (in % by weight of metal oxide) of at least 90 wt.%, preferably at least 95 wt.%, more preferably at least 98 wt.% of the metal concentration in the first hydrotreatment catalyst, or wherein the metal is added in such an amount that the catalyst obtained after step f) comprises Group VI metal in an amount of 5-40 wt.%, preferably 10-38 wt.%, more preferably 15-35 wt.%, calculated as trioxide and Group VIII metal in an amount of 1-10 wt.%, preferably 2-8 wt.%, and preferably further comprises phosphorus in an amount of 1-10 wt.%, calculated as PO.
4. The method according to claim 2 or 3, wherein step g) of contacting the heat-treated shaped mixture with a solution comprising a Group VI and / or Group VIII metal is performed during step f), wherein the solution comprising a Group VI and / or Group VIII metal further comprises the restoring agent.
5. The process according to any one of the preceding claims, wherein the first hydroprocessing catalyst comprises a regenerated catalyst obtained by regenerating a spent catalyst.
6. A process according to any one of the preceding claims, wherein the mixture comprises at least 70 wt.-%, preferably at least 80 wt.-%, more preferably at least 85 wt.-%, even more preferably at least 90 wt.-%, most preferably at least 95 wt.-% catalyst fines, based on the dry weight of the mixture.
7. The process according to any one of the preceding claims, wherein the binder comprises an inorganic oxide, preferably one or more selected from the group consisting of alumina, silica, silica-alumina, magnesia, combinations thereof, salts thereof and clays, preferably alumina or alumina-silica, most preferably gamma-alumina, and wherein the binder preferably comprises a material similar to or the same as the binder material in the first hydroprocessing catalyst.
8. The process according to any one of the preceding claims, wherein the catalyst fines have a D50 particle size, or the first hydroprocessing catalyst is ground to form catalyst fines having a D50 particle size, which is less than 200 μm, preferably less than 100 μm, more preferably less than 50 μm, even more preferably less than 30 μm, and preferably greater than 1 μm, more preferably greater than 2 μm, and even more preferably greater than 4 μm, and preferably has a D90 of less than 500 μm, preferably less than 200 μm, more preferably less than 100 μm and even more preferably less than 80 μm and preferably greater than 1 μm, more preferably greater than 2 μm and even more preferably greater than 4 μm.
9. The method according to any one of the preceding claims, wherein the heat treated shaped mixture comprises: at least 80 wt%, preferably at least 85 wt% catalyst fines; 0.3-0.7 mL / g, more preferably 0.3-0.6 mL / g total pore volume; 0.005-0.15 mL / g, preferably 0.005-0.1 mL / g, more preferably 0.005-0.06 mL / g Macropore volume above 120 and 300m 2 / g, preferably between 145 and 280m 2 / g of surface area SA; and at least 2 lbs / mm, more preferably at least 3 lbs / mm and more preferably at least 4 lbs / mm of side crush strength (SCS).
10. The method according to any one of the preceding claims, further comprising an aging step h) after the recovery step f), wherein the aging is preferably carried out at a temperature between 20°C and 100°C, preferably between 30°C and 80°C, and preferably lasts for a time of less than 18 hours, preferably less than 15, 10, 7, 4 hours or less than 2 hours, and more preferably between 0.5 and 2 hours, even more preferably between 0.5 and 1 hour.
11. The method according to any one of the preceding claims, wherein the restoring agent reduces the crystalline fraction of the metal oxide in the heat-treated forming mixture by preferably at least 20%, preferably at least 30%, or more preferably at least 40%, whereby the crystalline fraction of the metal oxide is preferably below 5 weight percent, more preferably below 2.5 weight percent.
12. A method according to any one of the preceding claims, wherein the restoring agent comprises a complexing agent, preferably a carboxylic acid comprising at least one carboxyl group and 1 to 20 carbon atoms, preferably citric acid or lactic acid, and preferably comprises in addition to the complexing agent an organic additive, the organic additive preferably being selected from the group of compounds comprising at least two hydroxyl groups and 2 to 10 carbon atoms per molecule and ethers or polyethers of these compounds, wherein preferably the restoring agent is lactic acid, or a combination of citric acid and the organic additive.
13. A hydroprocessing catalyst obtainable by the method according to any one of claims 1 to 12, preferably having a total pore volume of 0.2-1.0 mL / g, more preferably 0.3-0.7 mL / g, even more preferably 0.3-0.6 mL / g; preferably having a total pore volume of 0.005-0.3, more preferably 0.005-0.1 mL / g, even more preferably 0.005-0.06 mL / g. Preferably, the pore volume is between 100 and 300 m 2 / g, more preferably between 120 and 300m 2 / g, even more preferably between 145 and 280 m 2 / g, and preferably has a side crush strength (SCS) of at least 2 lbs / mm, more preferably at least 3 lbs / mm, and more preferably at least 4 lbs / mm.
14. A heat-treated shaped mixture for use as a support for preparing a hydroprocessing catalyst, comprising: at least 80 wt%, preferably at least 85 wt%, of catalyst fines, having a total pore volume of 0.3-0.7 mL / g, more preferably 0.3-0.6 mL / g, The macropore volume is 0.005-0.15, preferably 0.005-0.1 mL / g, more preferably 0.005-0.06 mL / g, and the surface area SA is between 120 and 300 m 2 / g, preferably between 145 and 280m 2 / g, and preferably the side crush strength (SCS) is at least 2 lbs / mm, more preferably at least 3 lbs / mm, and more preferably at least 4 lbs / mm.
15. A process for the hydroprocessing of a hydrocarbon feedstock, wherein the hydrocarbon feedstock is contacted under hydroprocessing conditions with a catalyst according to claim 13 or a catalyst obtained by a process according to any one of claims 1 to 12, the catalyst optionally having been dried and optionally having been (pre)sulfurized before contact with the hydrocarbon feedstock, wherein the hydrocarbon feedstock is preferably a naphtha, VGO type diesel feedstock.
Citation Information
Patent Citations
Process for activating a hydrotreating catalyst
EP1680486A1
Hydrotreating of petroleum residuum using shaped catalyst particles of small diameter pores
US4028227A
Use of citric acid to make catalyst from catalyst fines
US4107087A
A hydroprocessing catalyst prepared with waste catalyst fines and its use
WO2012021386A1